Mechanical Characterization and Tensile Fractography of Al7075-WCP-CoP Composite (Fracture and Structural Integrity, 2022)
The demand for materials with an unusual combination of properties has increased tremendously at a level that cannot be attained through the use of conventional materials. This is especially true for materials used in aircraft, automotive and power generation applications. The microstructure and mechanical properties of Al7075 – 6, 9 and 12 wt.% WC-Co particles reinforced composites are shown in this study. Liquid metallurgy is used to create the composites. The planetary ball milling method is utilized to turn the WC-Co mixtures into cermets, and the particles with a size range of 30-40 µm are employed as reinforcement. SEM and EDS analyses were used to characterise the microstructure. ASTM standards are used to test the mechanical characteristics of both as cast Al7075 and Al7075-6, 9 and 12 wt.% WC-Co composites. SEM was used to perform fractography study on the prepared composite.
Keywords: Al7075; cermet; Liquid Melt Method; Mechanical Behavior; Fractography